CHANGES IN THE POLICY OF THE SOVIET STATE REGARDING ISLAMIC RELIGION AND EDUCATION - Murodov Shuhrat Komil ugli (Journal of Learning on History and Social Sciences, 2024)
With the establishment of Soviet power in 1917, the ideology of forming a Soviet personality in a new form was put forward. This led to the abolition of traditional educational institutions in the country - old-style schools and madrasahs. Changes in the political situation during World War II led to the establishment of an important religious office in the region in 1943 - the Religious Office of the Muslims of Central Asia and Kazakhstan